From Shared Past to Common Future: A Historical Review of Indonesia-Malaysia Relations - Yanuardi Syukur (Centre for Asian Social Science Research (CASSR), Faculty of Social and Political Sciences, UIN Sunan Gunung Djati Bandung, 2025)
This paper explores the historical ties between Indonesia and Malaysia by tracing the European pursuit of spices, which led to colonial domination in the region. Central to this history is the strategic role of the Strait of Malacca as a vital corridor for trade and cultural exchange, and the significance of Ternate's spices as a highly valued commodity. These interactions brought together diverse ethnic groups—including Malay and European traders—forming a foundation of cooperation that can inspire present and future relations. Following the end of colonialism, Indonesia and Malaysia, as part of the broader Malay world, embarked on a quest for national and collective identity. Shared cultural, linguistic, historical, and religious ties offer valuable social capital that can be leveraged to foster deeper regional collaboration. This paper argues that revisiting and revitalizing shared historical narratives—especially through joint academic, civil society, and community-based initiatives—can enhance mutual understanding and cooperation. In an increasingly globalized world, drawing on this common past can contribute to building a more stable and integrated future for Indonesia, Malaysia, and the wider Malay world.